Ethylene / alpha-olefin copolymer as well as preparation method and application thereof
By using a specific design of ethylene/α-olefin copolymer in the photovoltaic film, its crosslinking activity and vulcanization speed are improved, and the problem of slow vulcanization speed of photovoltaic film is solved, achieving higher processing efficiency and product stability.
Patent Information
- Application Number
- CN202411686431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The vulcanization rate of existing photovoltaic adhesive films is slow, resulting in a long processing time for lamination crosslinking reactions, limiting the production efficiency and product stability of photovoltaic modules.
Ethylene/α-olefin copolymer is used, and the molar percentage of the α-olefin ternary sequence EXXXE is 4.5%-13%. The activity and crosslinking degree of crosslinking active sites are improved by fine chain structure design, reducing the damage of α-olefins to the crystalline segment of ethylene, and achieving faster vulcanization crosslinking reaction.
It significantly improves the processing speed and film strength of photovoltaic packaging materials, shortens the cross-linking time, reduces the use of cross-linking additives, reduces the production cost, and ensures the long-term stability of photovoltaic modules and high power generation efficiency.
Smart Images

Figure BDA0005149859590000081 
Figure BDA0005149859590000181 
Figure BDA0005149859590000191
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an ethylene / alpha-olefin copolymer and a preparation method and application thereof. Background Art
[0002] In recent years, the demand for photovoltaics has grown rapidly, and the global demand for adhesive films has also risen accordingly. With the rise of double-glass modules and N-type battery technology, the industry's demand for POE (polyolefin elastomers, including POE and EPE) adhesive films has also increased significantly due to their better packaging performance. Photovoltaic adhesive films play a vital role in the photovoltaic industry chain. Although their cost only accounts for about 6% of the total cost of photovoltaic modules, it is essential to ensure the durability and power generation efficiency of the modules. POE is a thermoplastic polyolefin elastomer obtained by copolymerizing ethylene and α-olefins using a solution polymerization process. It shows better compatibility with N-type TOPCon photovoltaic modules due to its excellent water vapor barrier rate, weather resistance and PID resistance. EPE adhesive film combines the advantages of POE and EVA (ethylene-vinyl acetate copolymer) resins, and is also an important direction for the development of adhesive films.
[0003] With the development of photovoltaic technology, higher requirements are placed on the production efficiency and product stability of photovoltaic modules. Based on the actual processing requirements of the module film, how to improve the vulcanization speed of the photovoltaic film, thereby shortening the processing time of the lamination cross-linking reaction, and achieving greater cost reduction and efficiency improvement has important application value. In order to speed up the vulcanization speed of POE photovoltaic film, the main solutions in the industry are currently to optimize the film formula, optimize the cross-linking process, or modify the POE particles by means of silane grafting. For example, CN116023891A discloses a modified POE composition for photovoltaic adhesive film, whose raw material composition includes: 50-75% POE resin, 15-40% cross-linking sensitized polymer, 1-3% vinyl silane, 1-3% glycidyl methacrylate, 0.1-0.5% initiator, 0.5% antioxidant, 0.5% light stabilizer, 1-5% liquid cross-linking agent; the film is modified by chemical grafting to graft silane monomers onto POE macromolecular chains to form a high molecular weight tackifier, thereby contributing to the cross-linking degree of the film curing through silane cross-linking, thereby increasing the cross-linking speed of the film and shortening the curing cycle. CN115873528A discloses a fast cross-linking packaging material, comprising the following components: 90-99% of a base material, 0.6-1.5% of a cross-linking agent, 0.5-2% of a co-cross-linking agent, 0.1-1% of a coupling agent, 0.1-0.5% of an antioxidant, and 0.1-0.5% of a light stabilizer; the cross-linking agent comprises tert-amyl peroxide-2-ethylhexyl carbonate, which is combined with other components to optimize the cross-linking formula of the adhesive film, thereby accelerating the cross-linking speed and improving the production efficiency of the components. CN110713798A discloses a fast cross-linking packaging adhesive film for volt-on modules, comprising the following components: 0-30 parts by mass of a base resin, 30-100 parts by mass of a first modified resin, 0-50 parts by mass of a second modified resin, 0.01-3 parts by mass of an organic peroxide, 0.02-2 parts by mass of a silane coupling agent, 0.005-2 parts by mass of a light stabilizer, and 0-20 parts by mass of a pigment; the first modified resin is one or more of ethylene and vinyl acetate, propylene, butene, hexene or octene copolymers containing at least two active groups, mixed in any ratio, wherein the active groups are selected from amino, carboxyl, hydroxyl, mercapto, anhydride, sulfonic acid, epoxy, cyano, isocyanate, silane coupling, and acyl chloride; the adhesive film uses the modified resin to replace a small molecule auxiliary cross-linking agent to improve the cross-linking reaction of the adhesive film, and combined with radiation or heat pretreatment, the component lamination time can be shortened and the component manufacturing efficiency can be effectively improved.
[0004] Although the industry has proposed solutions to improve the crosslinking rate from the perspectives of adjusting the auxiliary agent components, chemical modification, and improving the crosslinking process, these solutions all require matching specific formulation systems or process procedures, which not only bring great limitations to the preparation of the film and the encapsulation of photovoltaic modules, increasing costs, but also the addition of modified auxiliary agents may have an adverse effect on the long-term stability of photovoltaic modules. Therefore, the development of a new material with universal applicability that does not rely on specific crosslinking auxiliary agents and crosslinking processes to improve the processing efficiency of photovoltaic modules is an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an ethylene / α-olefin copolymer and a preparation method and application thereof. The ethylene / α-olefin copolymer has a specific α-olefin ternary sequence content, which improves the cross-linking vulcanization speed and cross-linking degree from the perspective of the intrinsic fine chain structure, while taking into account good melt fluidity, and can be widely used in packaging materials for photovoltaic modules. Without requiring the regulation of cross-linking aids and cross-linking processes during the cross-linking process, the processing efficiency and yield of the modules are significantly improved.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an ethylene / α-olefin copolymer, wherein the molar percentage of the α-olefin ternary sequence EXXXE in the ethylene / α-olefin copolymer measured by nuclear magnetic resonance carbon spectroscopy is 4.5%-13%; wherein E represents a structural unit based on ethylene, and X represents a structural unit based on α-olefin.
[0008] In the ethylene / α-olefin copolymer provided by the present invention, a specific proportion of EXXXE sequence structure is contained in the polymer chain segment, and the α-olefin distribution is more uneven. Due to the uneven insertion of the α-olefin, the crosslinking active site of the polymer is more active under the same or similar insertion rate conditions, and the vulcanization crosslinking reaction can occur faster under the same conditions. At the same time, the uneven insertion of the α-olefin can reduce the damage of the α-olefin to the ethylene crystal segment, so that the polymer has a higher degree of crosslinking under the same or similar insertion rate conditions. The present invention designs the polymer from the perspective of the intrinsic fine chain structure, and provides an ethylene / α-olefin copolymer with high crosslinking reaction activity, high crosslinking vulcanization reaction speed and high crosslinking degree, while taking into account good melt fluidity. It is used for photovoltaic encapsulation materials, and does not require the regulation of the components and dosage of the crosslinking aid in the crosslinking process, and does not rely on the crosslinking process. On the basis of, the processing speed and film strength of the photovoltaic encapsulation material (such as encapsulation film) are significantly improved, and the use of the crosslinking aid can be reduced, which is of great significance to the cost reduction and efficiency improvement of photovoltaic modules.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] In the present invention, the ethylene / α-olefin copolymer is characterized by carbon nuclear magnetic resonance spectroscopy ( 13 The molar percentage of the α-olefin ternary sequence EXXXE measured by C-NMR is 4.5%-13%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, preferably 4.5%-11%.
[0011] Preferably, the melt index (MI) of the ethylene / α-olefin copolymer at 190°C and 2.16kg is 1-30g / 10min, for example, it can be 2g / 10min, 3g / 10min, 5g / 10min, 7g / 10min, 8g / 10min, 10g / 10min, 13g / 10min, 15g / 10min, 17g / 10min, 20g / 10min, 23g / 10min, 25g / 10min, 27g / 10min or 29g / 10min, further preferably 1.5-24g / 10min, and more preferably 3-22g / 10min.
[0012] Preferably, the density of the ethylene / α-olefin copolymer is 0.860-0.880 g / cm 3 , for example, it can be 0.862 g / cm 3 , 0.865g / cm 3 , 0.868g / cm 3 、0.870g / cm 3 , 0.872g / cm 3 , 0.875g / cm 3 or 0.878 g / cm 3 , and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and further preferably 0.862-0.880 g / cm 3 , more preferably 0.865-0.877 g / cm 3 .
[0013] Preferably, the ethylene / α-olefin copolymer is characterized by carbon nuclear magnetic resonance spectroscopy ( 13The molar percentage of sequence EXXE measured by C-NMR) is 9%-16%, for example, it can be 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% or 15.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0014] Preferably, the ethylene / α-olefin copolymer is characterized by carbon nuclear magnetic resonance spectroscopy ( 13 The molar percentage of sequence EXE measured by C-NMR) is 46%-69%, for example, it can be 47%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 64%, 65%, 66% or 68%, as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0015] Preferably, the weight average molecular weight (M) of the ethylene / α-olefin copolymer is w ) is 4.0×10 4 -15.0×10 4 g / mol, for example, 5.0×10 4 g / mol, 6.0×10 4 g / mol, 7.0×10 4 g / mol, 8.0×10 4 g / mol, 9.0×10 4 g / mol, 10.0×10 4 g / mol, 11.0×10 4 g / mol, 12.0×10 4 g / mol, 13.0×10 4 g / mol or 14.0×10 4 g / mol, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will no longer exhaustively list the specific values included in the range. A further preferred range is 4.5×10 4 -13.0×10 4 g / mol, more preferably 4.6×10 4 -9.0×10 4 g / mol.
[0016] Preferably, the molecular weight distribution index (PDI, M w / M n) is 2.0-3.0, for example, it can be 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or 2.9, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range, and further preferably is 2.0-2.7, and more preferably 2.1-2.6.
[0017] Exemplarily, the weight average molecular weight (M w ), number average molecular weight (M n ) is obtained by gel permeation chromatography (GPC); molecular weight distribution PDI is M w / M n .
[0018] Preferably, the α-olefin is selected from any one or a combination of at least two of C3-C20 α-olefins; wherein the C3-C20 α-olefin is specifically C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, and C20 α-olefins.
[0019] Preferably, the α-olefin includes any one of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene, or a combination of at least two thereof.
[0020] Preferably, the α-olefin is selected from any one or a combination of at least two of C3-C12 α-olefins, and more preferably any one or a combination of at least two of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, and 1-decene.
[0021] Preferably, the mass percentage of the α-olefin-based structural units in the ethylene / α-olefin copolymer is 20%-38%, for example, it can be 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35% or 37%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0022] Preferably, the molar insertion rate of α-olefin in the ethylene / α-olefin copolymer is 5%-50%, for example, it can be 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0023] In a second aspect, the present invention provides a method for preparing the ethylene / α-olefin copolymer as described in the first aspect, the preparation method comprising: polymerizing ethylene and α-olefin under the catalysis of a catalytic system to obtain the ethylene / α-olefin copolymer.
[0024] Preferably, the single-pass conversion rate of ethylene in the polymerization reaction is 80%-92%, for example, it can be 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or 91%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range, and 85%-90% is further preferred.
[0025] Preferably, the α-olefin conversion rate in the polymerization reaction is ≥26%, for example, it can be 26.5%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 38% or 40%, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range, and 26%-36% is further preferred.
[0026] As a preferred technical solution of the present invention, during the polymerization reaction, by controlling the ethylene single-pass conversion rate, the relative concentrations of ethylene and α-olefin at the reaction active center can be actually controlled, and the relative concentration of ethylene / α-olefin at the polymerization active center is one of the main influencing factors of the sequence distribution of the ethylene / α-olefin copolymerization process. Therefore, by controlling the ethylene single-pass conversion rate within the range of 80%-92% and controlling the α-olefin conversion rate to ≥26%, it is possible to improve the polymerization reaction activity while regulating the EXXXE sequence distribution so that the EXXXE sequence content is 4.5%-13%.
[0027] Preferably, the catalytic system comprises a combination of a main catalyst and a co-catalyst.
[0028] Preferably, the main catalyst is a homogeneous catalyst, preferably any one of a metallocene catalyst, a post-metallocene catalyst, and a non-metallocene catalyst, or a combination of at least two thereof.
[0029] Preferably, the main catalyst is a transition metal catalyst.
[0030] Preferably, the main catalyst includes methylsilyl (N-tert-butylamino) (tetramethylcyclopentadienyl) titanium dichloride, dimethylsilyl (N-tert-butylamino) (tetramethylcyclopentadienyl) dimethyl titanium, dimethylsilyl (N-tert-butylamino) (fluorenyl) titanium dichloride, (pentamethylcyclopentadienyl) trimethoxytitanium, dibenzylidene (cyclopentadiene) (9-fluorenyl) zirconium dichloride, dimethyldisilyl bis (2-methyl-4-phenyl-1-indenyl) zirconium dichloride), meso-dimethylsilyl bis (1-indenyl) zirconium dichloride, (bis (methylcyclopentadiene) zirconium dichloride), (bis (1,3-dimethylcyclopentadienyl) zirconium dichloride, (cyclopentadienyl) (1,2-dimethoxyethane) zirconium trichloride, Diphenylsilyl (cyclopentadiene) (9-fluorenyl) zirconium dichloride, racemic dimethylsilyl bis (2-methyl-1-indenyl) zirconium dichloride, dibenzhydryl cyclopentadiene (2,7-di-tert-butyl-fluorenyl) zirconium dichloride, di-p-toluene cyclopentadiene (2,7-di-tert-butyl-fluorenyl) zirconium dichloride, dimethylbis (propylcyclopentadienyl) hafnium, bis (n-butylcyclopentadiene) hafnium dichloride, dimethylsilyl bis (2-methyl-4-phenylindenyl) zirconium dichloride, rac-ethylene bis (1-indenyl) zirconium dichloride, any one or a combination of at least two of the compounds shown in formula A, the compounds shown in formula B, the compounds shown in formula C, the compounds shown in formula D, and the compounds shown in formula E.
[0031]
[0032] Wherein, Ph represents phenyl, Me represents methyl, and Et represents ethyl. i Pr represents isopropyl, Bn represents benzyl, n Bu represents n-butyl.
[0033] M is selected from Ti, Zr or Hf.
[0034] X is selected from halogen (eg, F, Cl, Br, I), methyl, benzyl, dimethylamino, and more preferably Cl or methyl.
[0035] R is selected from any one of a C1-C30 alkyl group and a C6-C30 aryl group.
[0036] wherein the C1-C30 alkyl group may be a straight or branched chain alkyl group of C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C20, C22, C24, C25, C26, C28, etc., and may also be a straight or branched chain alkyl group of C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C20, C22, C24, C25, C26, C28, etc. The invention relates to a cycloalkyl group of C20, C22, C24, C25, C26, C28, etc., and is further preferably a C1-C10 straight or branched alkyl group, a C3-C10 cycloalkyl group, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, 2-ethylhexyl, n-octyl, n-heptyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, adamantyl, etc.
[0037] The C6-C30 aryl group may be an aryl group of C6, C9, C10, C12, C14, C16, C18, C20, C22, C24, C26 or C28, etc., preferably a C6-C20 aryl group, illustratively including but not limited to phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthryl, etc.
[0038] Preferably, the main catalyst introduction amount is 0.05-0.2 g / h, for example, it can be 0.06 g / h, 0.08 g / h, 0.1 g / h, 0.11 g / h, 0.12 g / h, 0.13 g / h, 0.14 g / h, 0.15 g / h, 0.16 g / h, 0.17 g / h, 0.18 g / h or 0.19 g / h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 0.09-0.17 g / h is further preferred.
[0039] Preferably, the cocatalyst comprises an organoaluminum compound and optionally an organoboron compound.
[0040] Preferably, the organic aluminum compound includes any one of aluminoxane, an alkyl aluminum compound, and an alkyl aluminum chloride, or a combination of at least two thereof.
[0041] Preferably, the aluminoxane includes any one of methylaluminoxane (MAO), modified methylaluminoxane (MMAO), ethylaluminoxane, and butylaluminoxane, or a combination of at least two thereof.
[0042] Preferably, the alkyl aluminum compound includes any one of triethyl aluminum, triisobutyl aluminum, trioctylaluminum, trimethyl aluminum, tripropyl aluminum, tri-n-butyl aluminum, and tri-sec-butyl aluminum, or a combination of at least two thereof.
[0043] Preferably, the alkylaluminum chloride includes any one of ethylaluminum monochloride, ethylaluminum sesquichloride, and ethylaluminum dichloride, or a combination of at least two thereof.
[0044] Preferably, the molar ratio of Al in the organoaluminum compound to the transition metal in the main catalyst is (10-1000):1, for example, it can be 15:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 120:1, 140:1, 150:1, 160:1, 180:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1 or 950:1, etc., and further preferably (20-100):1.
[0045] Preferably, the organic boron compound includes any one of trityltetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)boron, N,N-dimethylanilinetetrakis(pentafluorophenyl)borate, dioctadecylmethyltertiaryaminetetrakis(pentafluorophenyl)borate, and dihydrogenated tallow methyltertiaryaminetetrakis(pentafluorophenyl)borate, or a combination of at least two thereof.
[0046] Preferably, the molar ratio of B in the organic boride to the transition metal in the main catalyst is ≤10:1, for example, it can be 0 (i.e., no organic boride is used), 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1 or 9.5:1, etc., and more preferably (1-3):1.
[0047] Preferably, the polymerization reaction is carried out in the presence of a solvent, that is, the polymerization reaction is a solution polymerization reaction.
[0048] Optionally, the solution polymerization reaction is carried out in one reactor or several (≥2) reactors connected in series.
[0049] The solvent is in a liquid or supercritical state under the conditions of the polymerization reaction, preferably in a liquid state.
[0050] Preferably, the solvent includes any one of an alkane solvent, a halogenated alkane solvent, a cycloalkane solvent, and an aromatic solvent, or a combination of at least two of them.
[0051] For alkane solvents and cycloalkane solvents, C5-C12 (e.g. C6, C7, C8, C9, C10, C11, etc.) alkanes and C5-C12 (e.g. C6, C7, C8, C9, C10, C11, etc.) cycloalkanes are preferred, which are unsubstituted or substituted with C1-C4 (e.g. C2, C3, C4) straight or branched alkyl groups; this type of solvent illustratively includes but is not limited to: any one or a combination of at least two of pentane, methylpentane, hexane, heptane, octane, cyclohexane, methylcyclohexane, hydrogenated naphtha, C6 mixed alkanes, and isoalkanes (e.g. Isopar E).
[0052] Preferably, the solvent comprises any one of pentane, methylpentane, n-butane, isobutane, methylcyclopentane, methylenecyclopentane, n-hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, isoparaffins (such as Isopar E), hydrogenated naphtha, benzene, toluene, and xylene, or a combination of at least two thereof.
[0053] Preferably, the polymerization reaction is carried out in the presence of a chain transfer agent.
[0054] Preferably, the chain transfer agent includes any one of methane, ethane, propane, and hydrogen, or a combination of at least two of them, and hydrogen is more preferred.
[0055] Preferably, the amount of hydrogen introduced is 0.005-0.5 g / h, for example, it can be 0.008 g / h, 0.01 g / h, 0.02 g / h, 0.05 g / h, 0.08 g / h, 0.1 g / h, 0.15 g / h, 0.2 g / h, 0.25 g / h, 0.3 g / h, 0.35 g / h, 0.4 g / h, 0.45 g / h, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range, and 0.01-0.3 g / h is further preferred.
[0056] Preferably, the ethylene feed rate is 5-15 kg / h, for example, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h, 10 kg / h, 11 kg / h, 12 kg / h, 13 kg / h or 14 kg / h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range.
[0057] Preferably, the feed rate of α-olefin is 10-30 kg / h, for example, it can be 12 kg / h, 15 kg / h, 18 kg / h, 20 kg / h, 22 kg / h, 25 kg / h or 28 kg / h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Preferably, the ratio of the amount of ethylene introduced to the amount of α-olefin introduced is 1:(1-3), for example, it can be 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8, etc., and more preferably 1:(1.2-2.2).
[0059] Preferably, the polymerization reaction temperature is 110-200°C, for example, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or 190°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 120-190°C is further preferred.
[0060] Preferably, the polymerization reaction pressure is 1-10 MPa, for example, it can be 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa or 9 MPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 3-7 MPa is further preferred.
[0061] As a preferred technical solution of the present invention, the temperature of the polymerization reaction is 110-200° C., and / or the pressure of the polymerization reaction is 1-10 MPa, so that the catalyst system maintains high catalytic and polymerization activity.
[0062] Preferably, the polymerization reaction time is 2-20 min, for example, it can be 3 min, 4 min, 5 min, 6 min, 8 min, 10 min, 12 min, 14 min, 15 min, 16 min or 18 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 3-12 min is further preferred.
[0063] Preferably, after the polymerization reaction is completed, the steps of quenching, devolatilization and extrusion granulation are also included.
[0064] In a preferred technical solution, the preparation method comprises the following steps:
[0065] Ethylene and α-olefin are polymerized in the presence of a catalyst system, hydrogen and a solvent to obtain the ethylene / α-olefin copolymer;
[0066] The catalytic system comprises a combination of a transition metal catalyst and a co-catalyst, the co-catalyst comprising an organoaluminum compound and optionally an organoboron compound;
[0067] The polymerization reaction temperature is 110-200°C, the pressure is 1-10MPa, and the time is 2-20min;
[0068] The single-pass conversion rate of ethylene in the polymerization reaction is 80%-92%, and the conversion rate of α-olefin is 26%-36%.
[0069] In a third aspect, the present invention provides a use of the ethylene / α-olefin copolymer as described in the first aspect in a photovoltaic encapsulation material.
[0070] In a fourth aspect, the present invention provides a photovoltaic encapsulation material, wherein the raw materials for preparing the photovoltaic encapsulation material include the ethylene / α-olefin copolymer as described in the first aspect.
[0071] Preferably, the photovoltaic encapsulation material comprises an encapsulation film.
[0072] Preferably, the preparation raw materials further include a cross-linking agent, a co-cross-linking agent and optionally other auxiliary agents.
[0073] Preferably, the cross-linking agent comprises an organic peroxide.
[0074] Preferably, the cross-linking agent includes any one or a combination of at least two of tert-amyl peroxy (2-ethylhexyl) carbonate, di (4-methylbenzoyl) peroxide, isopropyl benzene peroxide, di-tert-butyl peroxide, diisopropyl benzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, tert-butyl peroxy 2-ethylhexyl carbonate, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl peroxybenzoate, tert-butyl peracetate, and tert-butyl peroxy-3,5,5-trimethylhexanoate.
[0075] Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the cross-linking agent is 0.1-2 parts, for example, it can be 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.8 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0076] Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, and propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.
[0077] Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the co-crosslinking agent is 0.1-2 parts, for example, it can be 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.8 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0078] Preferably, the other additives include any one or a combination of at least two of a silane coupling agent, an antioxidant, a light stabilizer, an ultraviolet absorber, an anti-precipitation additive, and an anti-PID additive.
[0079] The present invention does not limit the specific types of other additives such as silane coupling agents, antioxidants, light stabilizers, ultraviolet absorbers, anti-precipitation additives, anti-PID additives, etc. Other additives known in the art that can be used for packaging materials are applicable to the present invention.
[0080] Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the silane coupling agent is 0.1-1 part, for example, it can be 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0081] Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the antioxidant is 0.1-1 part, for example, it can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or 0.9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0082] Preferably, the antioxidant includes any one of a hindered amine antioxidant, a hindered phenol antioxidant, and a phosphite antioxidant, or a combination of at least two thereof.
[0083] As a preferred technical solution of the present invention, the ethylene / α-olefin copolymer provided by the present invention has high cross-linking reaction activity, high cross-linking vulcanization reaction speed and high cross-linking degree. The photovoltaic encapsulation material (such as encapsulation film) prepared by the present invention has a faster cross-linking vulcanization speed and a higher cross-linking degree, which makes the film have a faster processing speed and higher film strength during processing, and can reduce the use of cross-linking agents, co-cross-linking agents and other cross-linking aids, which is of great significance for reducing costs and increasing output in photovoltaic module production. Based on the high cross-linking degree of the photovoltaic encapsulation material, it is ensured that the efficiency and performance of the encapsulated product are stable under long-term use, for example, the photovoltaic module has a higher power generation efficiency.
[0084] As a preferred technical solution of the present invention, the degree of cross-linking of the photovoltaic encapsulation material is greater than 80%, preferably greater than or equal to 82%, and may be 82.5%-86.1%.
[0085] As a preferred technical solution of the present invention, the cross-linking vulcanization time T90 of the photovoltaic encapsulation material is ≤12.5 min, and can be 11.6-12.31 min.
[0086] Illustratively, the method for preparing the photovoltaic encapsulation material comprises: blending and molding an ethylene / α-olefin copolymer, a cross-linking agent, a co-cross-linking agent and optionally other auxiliary agents to obtain the photovoltaic encapsulation material.
[0087] Preferably, the molding method comprises cast extrusion or twin-screw extrusion.
[0088] Compared with the prior art, the present invention has the following beneficial effects:
[0089] (1) The ethylene / α-olefin copolymer provided by the present invention has high cross-linking reaction activity, high cross-linking vulcanization reaction speed and high cross-linking degree through the special design of the intrinsic fine chain structure, especially the design of the EXXXE sequence structure, while taking into account good melt fluidity, and can be widely used in packaging materials for photovoltaic modules. Without requiring the regulation of the components and dosage of the cross-linking auxiliary agent in the cross-linking process and without relying on the cross-linking process, the processing speed and film strength of the photovoltaic packaging material are significantly improved.
[0090] (2) The photovoltaic encapsulation material provided by the present invention has a significantly improved cross-linking rate and degree of cross-linking based on the use of ethylene / α-olefin copolymer, which can shorten the processing time, improve the processing speed and efficiency, and reduce the use of cross-linking aids, which is of great significance to the cost reduction and efficiency improvement of photovoltaic modules. At the same time, the photovoltaic encapsulation material has a high degree of cross-linking and higher film strength, which can ensure the efficiency and stable performance of the encapsulated product in long-term use. DETAILED DESCRIPTION
[0091] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0092] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0093] "Optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes instances where the event occurs and instances where it does not.
[0094] In the following specific embodiments of the present invention, the main testing methods for polymers are as follows:
[0095] (1) Density: The test was conducted according to the method in standard ASTM D-792.
[0096] (2) Molecular weight (weight average molecular weight M w , number average molecular weight M n ), molecular weight distribution (PDI, M w / M n ) and the insertion rate of α-olefins can be obtained by gel permeation chromatography (GPC) testing. Specifically, chromatographic column: Agilent Olexis; solvent: 1,2,4-trichlorobenzene; flow rate: 1.0 mL / min; sample concentration: 1.0 mg / mL; injection volume: 200 μL; chromatographic column temperature: 160°C; detector: Agilent High Temperature RI detector; standard: polystyrene (PS) corrected with a cubic function.
[0097] (3) The molar percentage of sequence EXXXE, sequence EXXE, and sequence EXE was determined by carbon nuclear magnetic resonance spectroscopy ( 13C-NMR) test, specifically, 2.74g of the sample to be tested and tetrachloroethane-d2 containing 0.025M Cr(AcAc)3 (chromium acetylacetonate) were added to a NoreII1001-7 10mm NMR tube. The oxygen was removed by manually purging the tube with nitrogen for 1min using a Pasteur pipette. The tube and its contents were heated to 150°C using a heating block without using a heating gun as much as possible to dissolve and homogenize the sample. The sample was thoroughly mixed just before analysis and could not be cooled before being inserted into the heated NMR probe. This is necessary to ensure that the sample is uniform and representative of the entire sample. Data was collected using a Bruker 400MHz spectrometer equipped with a Bruker cryoprobe. Data were collected using 160 scans, a 6s pulse repetition delay, and a sample temperature of 120°C. All measurements were performed on non-spinning samples in locked mode. The sample was allowed to thermally equilibrate for 7min before data collection. The collected data are comprehensively used to calculate the sequence distribution of the polymer using the methods of Randall and Seger, and the aforementioned binary and ternary sequence distributions of the ethylene / α-olefin copolymer can be obtained respectively.
[0098] For randall's method, please refer to the literature: "A review of high resolution liquid13carbon nuclear magnetic resonance characterizations of ethylene-basedpolymers", Randall J C., Journal of Macromolecular Science-Reviews inMacromolecular Chemistry and Physics.1989, 29(2-3):201-317;
[0099] Seger's method can be found in the literature: "Quantitative 13 C NMR analysis of sequence distributions in poly(ethylene-co-1-hexene)", Seger MR et al., Analytical Chemistry., 2004, 76(19):5734-5747.
[0100] (4) Melt index (MI):
[0101] The melt indexer (CEAST melt indexer, Italy) was used for measurement. The method of national standard GB / T3682.1-2018 was adopted. The mass of the extrudate was weighed every 6 seconds at 190°C and 2.16 kg load. Five parallel operations were performed. The average value was taken and converted into the mass of the extrudate every 10 minutes, expressed in g / 10min.
[0102] (5) Ethylene single-pass conversion rate, α-olefin conversion rate:
[0103] Ethylene single-pass conversion = copolymer production rate × ethylene content in copolymer / ethylene feed rate;
[0104] α-olefin conversion rate = copolymer production rate × α-olefin content in copolymer / α-olefin feed rate;
[0105] The α-olefin content (mass content) and ethylene content (mass content) in the copolymer are measured by the above-mentioned GPC method; the copolymer production rate, ethylene feed rate and α-olefin feed rate are controlled by a continuous reaction device.
[0106] (6) Catalytic activity: Calculated according to the following formula: Catalytic activity = mass of copolymer (kg) / mass of main catalyst (g).
[0107] In the following specific embodiments of the present invention, the specific information of the materials used are as follows, all of which are commercially available chemicals:
[0108]
[0109] The ethylene / α-olefin copolymer and the preparation method thereof of the present invention will be described in detail below by taking a plurality of embodiments as examples, but the ethylene / α-olefin copolymer and the preparation method thereof of the present invention are not limited to these embodiments.
[0110] Example 1
[0111] An ethylene / α-olefin copolymer, the preparation method of which is as follows:
[0112] n-Hexane solvent (80 kg / h) and 1-butene (15 kg / h) were added to a 25 L autoclave continuous reactor, and then the temperature at the top of the reactor was preheated to 145° C. At the same time, the main catalyst A1 (0.167 g / h) and the cocatalyst methylaluminoxane (prepared into a n-hexane solution with an Al element content of 10 wt%, the solution feed rate was 0.80 g / h) were introduced into the reactor. Subsequently, ethylene (10 kg / h) and hydrogen (0.01 g / h) were added to the autoclave reactor, and the polymerization reaction was continuously carried out at a pressure of 3.5 MPa at 145° C. for more than 15 min to obtain a copolymer solution, and the ethylene single-pass conversion rate was controlled to be 92%, and the 1-butene conversion rate was 32.2%; after the reaction, the reaction solution was quenched with methanol and then entered into a three-stage devolatilization tank for devolatilization, and after unreacted hexane, 1-butene and ethylene were removed in the devolatilization tank, ethylene / α-olefin copolymer particles were obtained by extrusion granulation, and their properties were tested, as shown in Table 2.
[0113] Examples 2-8, Comparative Examples 1-2
[0114] An ethylene / α-olefin copolymer and a preparation method thereof, which differs from Example 1 only in that the catalyst and process parameters of the polymerization reaction are different, and the specific information is shown in Table 1; the process parameters not shown in Table 1 are the same as those in Example 1; the properties of the ethylene / α-olefin copolymer are shown in Table 2.
[0115] In Table 1, the feed amount (g / h) of the organoaluminum compound is the feed amount of its n-hexane solution (with an Al content of 10 wt%); the feed amount (g / h) of the organoboron compound is the feed amount of its n-hexane solution (with an organoboron compound content of 10 wt%). "--" indicates that the organoboron compound was not used.
[0116] Table 1
[0117]
[0118]
[0119] Table 2
[0120]
[0121]
[0122] Application Examples
[0123] A photovoltaic encapsulation material, specifically an encapsulation film, wherein the raw materials for its preparation include, by mass, 100 parts of an ethylene / α-olefin copolymer, 0.8 parts of a cross-linking agent (tert-amyl peroxy (2-ethylhexyl) carbonate), 0.7 parts of a co-cross-linking agent (triallyl isocyanurate), 0.3 parts of a silane coupling agent (3-(methacryloyloxy)propyltrimethoxysilane), and 0.2 parts of an antioxidant (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate); the ethylene / α-olefin copolymers are the ethylene / α-olefin copolymers provided in Examples 1-8 and Comparative Examples 1-2, respectively.
[0124] The preparation method of the packaging adhesive film comprises: mixing various preparation raw materials according to the formula amount, so that various additives are fully absorbed by the copolymer to obtain a mixed material; then adding the mixed material into a single-screw cast-film extruder, melting and plasticizing the mixed material, and then injecting it into a T-type die head, with a melting temperature of 90° C., and undergoing the processes of melt extrusion, cast film formation, cooling, slitting and winding to obtain the packaging adhesive film.
[0125] The encapsulation film is subjected to the following performance tests:
[0126] (1) Degree of cross-linking: The degree of cross-linking was determined according to the method in Photovoltaic Industry Association Standard T / CPIA0006-2017;
[0127] (2) Crosslinking vulcanization time T90: The optimal vulcanization time T90 of the film was measured according to the standard GB / T 16584-1996. T90 is used to characterize the speed of crosslinking. The smaller the T90 time, the faster the crosslinking speed.
[0128] The test results are shown in Table 3:
[0129] Table 3
[0130] Ethylene / α-olefin copolymer Crosslinking degree (%) T90(min) Example 1 83.5 11.73 Example 2 84.7 11.67 Example 3 85.4 11.78 Example 4 86.2 11.9 Example 5 82.5 11.85 Example 6 83.5 11.93 Example 7 85.4 12.01 Example 8 86.1 12.31 Comparative Example 1 79 12.57 Comparative Example 2 76 13.51
[0131] Combining the data in Tables 1 to 3, it can be seen that the ethylene / α-olefin copolymers provided in Examples 1-8 of the present invention and Comparative Examples 1-2 have similar melt index MI and density conditions, and by controlling the EXXXE sequence content within a specific range of 4.5%-13%, the ethylene / α-olefin copolymers have a higher degree of crosslinking and a faster crosslinking speed, which can significantly shorten the crosslinking time of the packaging material, making T90 ≤ 12.31 min, thereby improving the processing efficiency; at the same time, the degree of crosslinking of the packaging film is 82.5%-86.1%, and its higher degree of crosslinking can ensure the efficiency of the packaged product under long-term use, for example, the battery cell has a higher power generation efficiency.
[0132] In summary, the present invention can optimize the cross-linking performance of the copolymer in the process of preparing the film by specially designing the EXXXE sequence and the intrinsic fine chain structure of the ethylene / α-olefin copolymer.
[0133] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the ethylene / α-olefin copolymer and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An ethylene / α-olefin copolymer, characterized in that: The molar percentage of the α-olefin ternary sequence EXXXE in the ethylene / α-olefin copolymer measured by carbon nuclear magnetic resonance spectroscopy is 4.5%-13%, wherein E represents a structural unit based on ethylene, and X represents a structural unit based on α-olefin.
2. The ethylene / α-olefin copolymer according to claim 1, characterized in that The ethylene / α-olefin copolymer has a melt index of 1-30 g / 10 min at 190° C. and 2.16 kg; Preferably, the density of the ethylene / α-olefin copolymer is 0.860-0.880 g / cm 3 .
3. The ethylene / α-olefin copolymer according to claim 1 or 2, characterized in that The molar percentage of the sequence EXXE in the ethylene / α-olefin copolymer measured by carbon nuclear magnetic resonance spectroscopy is 9%-16%; Preferably, the molar percentage of the sequence EXE in the ethylene / α-olefin copolymer measured by carbon nuclear magnetic resonance spectroscopy is 46%-69%.
4. The ethylene / α-olefin copolymer according to any one of claims 1 to 3, characterized in that The molecular weight distribution index of the ethylene / α-olefin copolymer is 2.0-3.0; Preferably, the weight average molecular weight of the ethylene / α-olefin copolymer is 4.0×10 4 -15.0×10 4 g / mol, more preferably 4.5×10 4 -13.0×10 4 g / mol.
5. The ethylene / α-olefin copolymer according to any one of claims 1 to 4, characterized in that The α-olefin is selected from any one or a combination of at least two of C3-C20 α-olefins; Preferably, the α-olefin is selected from any one or a combination of at least two of C3-C12 α-olefins, and more preferably any one or a combination of at least two of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, and 1-decene; Preferably, the mass percentage of the structural units based on α-olefin in the ethylene / α-olefin copolymer is 20%-38%.
6. A method for preparing an ethylene / α-olefin copolymer according to any one of claims 1 to 5, characterized in that: The preparation method comprises: ethylene and α-olefin are polymerized under the catalysis of a catalytic system to obtain the ethylene / α-olefin copolymer.
7. The preparation method according to claim 6, characterized in that: The ethylene per-pass conversion rate in the polymerization reaction is 80%-92%; Preferably, the α-olefin conversion rate in the polymerization reaction is ≥26%, more preferably 26%-36%; Preferably, the catalytic system comprises a combination of a main catalyst and a co-catalyst, wherein the main catalyst is a transition metal catalyst; Preferably, the cocatalyst comprises an organoaluminum compound and optionally an organoboron compound; Preferably, the organoaluminum compound comprises any one or a combination of at least two of aluminoxane, alkylaluminum compound, and alkylaluminum chloride; Preferably, the aluminoxane includes any one of methylaluminoxane, modified methylaluminoxane, ethylaluminoxane, and butylaluminoxane, or a combination of at least two thereof; Preferably, the alkyl aluminum compound includes any one or a combination of at least two of triethyl aluminum, triisobutyl aluminum, trioctylaluminum, trimethyl aluminum, tripropyl aluminum, tri-n-butyl aluminum, and tri-sec-butyl aluminum; Preferably, the alkylaluminum chloride includes any one of ethylaluminum monochloride, ethylaluminum sesquichloride, and ethylaluminum dichloride, or a combination of at least two thereof; Preferably, the molar ratio of Al in the organoaluminum compound to the transition metal in the main catalyst is (10-1000):1, more preferably (20-100):1; Preferably, the organic boron compound includes any one of trityl tetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)boron, N,N-dimethylaniline tetrakis(pentafluorophenyl)borate, dioctadecylmethyl tertiary amine tetrakis(pentafluorophenyl)borate, and dihydrogenated tallow methyl tertiary amine tetrakis(pentafluorophenyl)borate, or a combination of at least two thereof; Preferably, the molar ratio of B in the organic boron compound to the transition metal in the main catalyst is ≤10:
1.
8. The preparation method according to claim 6 or 7, characterized in that: The polymerization reaction is carried out in the presence of a solvent; Preferably, the solvent comprises any one of pentane, methylpentane, n-butane, isobutane, methylcyclopentane, methylenecyclopentane, n-hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, isoparaffin, hydrogenated naphtha, benzene, toluene, and xylene, or a combination of at least two thereof; Preferably, the polymerization reaction is carried out in the presence of a chain transfer agent; Preferably, the chain transfer agent includes any one of methane, ethane, propane, and hydrogen, or a combination of at least two thereof, and hydrogen is further preferred; Preferably, the polymerization reaction temperature is 110-200°C, more preferably 120-190°C; Preferably, the polymerization reaction pressure is 1-10 MPa, more preferably 3-7 MPa; Preferably, the polymerization reaction time is 2-20 min, more preferably 3-12 min.
9. Use of the ethylene / α-olefin copolymer according to any one of claims 1 to 5 in photovoltaic encapsulation materials.
10. A photovoltaic encapsulation material, characterized in that: The raw material for preparing the photovoltaic encapsulation material comprises the ethylene / α-olefin copolymer according to any one of claims 1 to 5; Preferably, the preparation raw materials further include a cross-linking agent, a co-cross-linking agent and optionally other auxiliary agents; Preferably, the cross-linking agent comprises an organic peroxide; Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the crosslinking agent is 0.1-2 parts; Preferably, based on 100 parts by mass of the ethylene / α-olefin copolymer, the mass of the auxiliary cross-linking agent is 0.1-2 parts; Preferably, the other additives include any one or a combination of at least two of a silane coupling agent, an antioxidant, a light stabilizer, an ultraviolet absorber, an anti-precipitation additive, and an anti-PID additive.
Citation Information
Patent Citations
Rapid cross-linking packaging adhesive film for photovoltaic module and preparation method
CN110713798A
Rapid cross-linking packaging material and preparation method and application thereof
CN115873528A
Modified POE (Polyolefin Elastomer) composition for photovoltaic adhesive film as well as preparation method and application of modified POE composition
CN116023891A
Ethylene / alpha-olefin block interpolymers
CN101983213A
High light transmittance ethylene / alpha-olefin copolymers
CN116789884A
Cited By
Ethylene / alpha-olefin copolymer, preparation method and application
CN121537550A